"He Says, She Says": Sexism and Sexual Harassment in Higher Educational Institutions of India. Issue 2 (3rd April 2022) - Mukherjee, Annesha; Dasgupta, Satyaki
Abstract: Results of a survey among current and former female students of colleges and universities in India show that subtle and explicit sexist practices are perpetuated in campus spaces by both male students and faculty members. Moreover, one in ten respondents reported being sexually assaulted by at least one person from their educational institutions. Further, we present a dynamic three-player game-theoretic model. The results highlight the role of institutions in lowering incidences of sexual harassment, and also incorporate the feminist critic of institutional responses in this context, thereby underlining the crucial role of both institutional action and cultural norms.